Pendampingan Sertifikasi Halal Produk Krupuk Mbah Bayin di Desa Kembangan, Bobang, Semen - Alifatu Nazila, Ulil; Wijayas, Ach. Sultan Hadi; Martin, Kenia Zulqi; Imami, Cucan; Sari, Erra Vazira Kurnia; Mutafarida, Binti (Welfare : Jurnal Pengabdian Masyarakat, 2023)
Halal certification is currently an important factor in MSMEs, especially for food products such as Krupuk Mbah Bayin in Kembangan, Bobang, and Semen Villages. This assistance to halal certification for MSMEs aims to increase understanding of the importance of halal certification with the hope of increasing the selling value of products and consumer buying interest. The implementation of the Student Creativity Program (PKM) uses lecture, tutorial, and discussion methods to provide a better understanding of MSME Krupuk Mbah Bayin. The results show that these MSMEs now understand the importance of halal certification and understand the procedures. Through direct assistance, MSMEs are given assistance in processing halal certification. It is hoped that this can increase consumer interest and trust in the presence of a halal label. In this way, it is hoped that product sales will increase, having a positive impact on the welfare of the community in Kembangan Village, Bobang, Semen, and Kediri Regency.